Гидрогеологические условия газоносности Днепровско-Донецкой впадины на больших глубинах - Терещенко, В.А.; Tereshchenko, B.A. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2008)
Рассматриваются закономерности распространения залежей газа в Днепровско-Донецкой впадине на глубинах более 4 км. Проанализированы гидрогеологические особенности природных резервуаров, состав подземных вод и природных газов на больших глубинах. Определены факторы формирования промышленных залежей. The regularities of distribution of natural gas deposits in Dnieper- Donets Basin on the depths more than 4 km are examined. Hydrogeological peculiarities of natural reservoirs, composition of reservoir waters and natural gases on the great depths are analyzed. The factors of formation of commercial reserves are determined.
The hydrogeological conditions of gas bearing of Dnieper-Donets basin on the great depths
Keywords: газоносность больших глубин; сверхгидростатические пластовые давления; gas of great depths; abnormal high pressures; газоносність великих глибин; надгідростатичні пластові тиски